HER3 expression is enhanced during progression of lung adenocarcinoma without EGFR mutation from stage 0 to IA1. Issue 4 (23rd February 2018) - Kumagai, Toru; Tomita, Yasuhiko; Nakatsuka, Shin‐ichi; Kimura, Madoka; Kunimasa, Kei; Inoue, Takako; Tamiya, Motohiro; Nishino, Kazumi; Susaki, Yoshiyuki; Kusu, Takashi; Tokunaga, Toshiteru; Okami, Jiro; et al.
Abstract : Background: Activating EGFR mutations, HER2, and HER3 are implicated in lung cancer; however, with the exception of EGFR gene amplification in lung adenocarcinoma harboring EGFR mutations, their involvement in disease progression during the early stages is poorly understood. In this paper, we focused on which receptor is correlated with lung adenocarcinoma progression in the presence or absence of EGFR mutation from stage 0 to IA1. Methods: HER2 and HER3 expression and activating EGFR mutations in surgically resected lung adenocarcinoma exhibiting ground glass nodules on chest computed tomography and re‐classified to stage 0 and IA1 were examined by immunohistochemistry and peptide nucleic acid‐locked nucleic acid PCR clamp method, respectively. Results: HER2 and HER3 expression was detected in 22.2% and 86.1% of samples, respectively. The frequency of EGFR mutation was 45.7% and was not significantly different between stage 0 and IA1 (40.0% and 48.0%, respectively), suggesting that EGFR mutation does not correlate with cancer progression from stage 0 to IA1. HER2 expression also did not correlate to progression. However, not only the frequency, but also the intensity of HER3 expression was increased in stage IA1 lung adenocarcinoma, particularly in lung adenocarcinoma without EGFR mutation. Conclusion: HER3 tends to be intensively expressed during the progression of lung adenocarcinoma without EGFR mutation from carcinoma in situ to invasive carcinoma.